A review on the properties of electrospun cellulose acetate and its application in drug delivery systems: A new perspective - Wsoo, Mohammed Ahmad; Shahir, Shafinaz; Mohd Bohari, Siti Pauliena; Mat Nayan, Nadirul Hasraf; Abd Razak, Saiful Izwan (Elsevier, 2020)
Cellulose acetate (CA) is a remarkable biomaterial most extensively used in biomedical applications due to their properties. This review highlighted the synthesis and chemical structure of CA polymer as well as focused on the mechanical, chemical, thermal, biocompatible, and biodegradable properties of electrospun CA nanofibers. These properties are essential in the evaluation of the CA nanofibers and provide information as a reference for the further utilization and improvement of CA nanofibers. Moreover, we have summarized the use of electrospun CA nanofibers in the drug delivery system as a carrier for drugs and classify them according to the drug class, including anti-inflammatory, anticancer, antioxidant, antimicrobial agents, vitamins and amino acids. Our review has been concluded that CA nanofibers cannot wholly be biodegraded within the human body due to the absence of cellulase enzyme but degraded by microorganisms. Hence, the biodegradation of CA nanofibers in vivo has addressed as a critical challenge.